2010
DOI: 10.1242/jeb.034371
|View full text |Cite
|
Sign up to set email alerts
|

The distinction between retractor and protractor muscles of the freshwater snail's male organ has no physiological basis

Abstract: SUMMARYMany animals are equipped with organs that can be everted, a notable example being male copulatory organs. The ability to protrude or evert an organ generally requires protractor and retractor muscles. Male copulatory behaviour of the pond snail Lymnaea stagnalis (L.) involves eversion (protraction) and retraction of the relatively large penis-carrying organ. For this preputium, protractor and retractor muscle bands have been defined, which implies eversion and retraction through the activity of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The eversion has been suggested to be facilitated by the existing hydrostatic pressure in the head sinus or an increased pressure in the arteria penis (Bekius, 1972; see also De Boer et al, 2010). De Lange et al (1998a) speculated that alternate contraction of longitudinal muscles inside and near the body wall and relaxation of circular preputium muscles near the body wall could also contribute to the subsequent full eversion of the preputium.…”
Section: Male Reproductive Behavior and Its Neuro-endocrine Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The eversion has been suggested to be facilitated by the existing hydrostatic pressure in the head sinus or an increased pressure in the arteria penis (Bekius, 1972; see also De Boer et al, 2010). De Lange et al (1998a) speculated that alternate contraction of longitudinal muscles inside and near the body wall and relaxation of circular preputium muscles near the body wall could also contribute to the subsequent full eversion of the preputium.…”
Section: Male Reproductive Behavior and Its Neuro-endocrine Controlmentioning
confidence: 99%
“…The retraction of the penis is most likely regulated by relaxation of the aforementioned preputium muscles and a decrease in the hydrostatic pressure. For the much larger preputium, retraction seems to require the preputium retractor muscles, because when this set of muscles is cut these snails are incapable of retracting the organ (De Boer et al, 2010). The preputium retractor muscles are affected by many of the identified substances, as summarized in Table 3, and their effects are in concordance with the presence of nerve fibers containing these substances.…”
Section: Male Reproductive Behavior and Its Neuro-endocrine Controlmentioning
confidence: 99%
“…Previous work has used approaches through the body wall to lesion or record either from nerves 13,14 , or muscles 15,16,17 . In our laboratory, we have anecdotally observed that body wall incisions are often accompanied by a significant loss of hemolymph and thus of body volume.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in agreement with the heptapeptides S/GDPFLRFamide having been shown to have a relaxing effect on the penis retractor muscle (PRM), involved in male copulation (van Golen et al 1995a ). In view of this inhibitory effect of the heptapeptides on its targets, it seems contradictory to assume that these neuropeptides are responsible for the contraction of the PRM needed for keeping the preputium inside the body wall of the snail to prevent male copulation activity (de Boer et al 2010 ). However, since the heptapeptides are co-expressed with other putative neuropeptides (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral male reproductive organs are innervated by a single nerve called nervus penis (NP, penial nerve) that originates from the right cerebral ganglion and travels along the muscular preputium (the penis-carrying organ in snails). There, it divides into three branches innervating different parts of the reproductive tract known as the penial complex composed of the preputium carrying the penis, the vas deferens and the retractor muscles (Koene 2010 ; de Boer et al 2010 ). The central neuronal network that innervates the penial complex includes various peptidergic neurons that can be divided in two categories: (i) clustered cells, forming the whole anterior and ventral lobe of the right cerebral ganglion and the I-cluster of the right pedal ganglion (de Boer et al 1997 ; van Duivenboden 1984 ; Smit et al 1992 ), and (ii) dispersed cells in the right pleural and parietal ganglia (van Duivenboden 1984 ).…”
Section: Introductionmentioning
confidence: 99%